Regulation of biomaterial implantation-induced fibrin deposition to immunological functions of dendritic cells. (March 2022) - Hu, Wenhui; Wang, Yun; Chen, Jin; Yu, Peng; Tang, Fuzhou; Hu, Zuquan; Zhou, Jing; Liu, Lina; Qiu, Wei; Ye, Yuannong; Jia, Yi; Zhou, Shi; et al.
Abstract: The performance of implanted biomaterials is largely determined by their interaction with the host immune system. As a fibrous-like 3D network, fibrin matrix formed at the interfaces of tissue and material, whose effects on dendritic cells (DCs) remain unknown. Here, a bone plates implantation model was developed to evaluate the fibrin matrix deposition and DCs recruitment in vivo . The DCs responses to fibrin matrix were further analyzed by a 2D and 3D fibrin matrix model in vitro . In vivo results indicated that large amount of fibrin matrix deposited on the interface between the tissue and bone plates, where DCs were recruited. Subsequent in vitro testing denoted that DCs underwent significant shape deformation and cytoskeleton reorganization, as well as mechanical property alteration. Furthermore, the immune function of imDCs and mDCs were negatively and positively regulated, respectively. The underlying mechano-immunology coupling mechanisms involved RhoA and CDC42 signaling pathways. These results suggested that fibrin plays a key role in regulating DCs immunological behaviors, providing a valuable immunomodulatory strategy for tissue healing, regeneration and implantation. Graphical abstract: Image 1